The shack revisited [compact disc, unabridged] : there is more going on here than you ever dared to dream - Kruger, C. Baxter (Hachette Audio, 2012)
Millions have found their spiritual hunger satisfied by William P. Young's #1 New York Times bestseller, "The Shack" the story of a man lifted from the depths of despair through his life-altering encounter with God the Father, God the Son, and God the Holy Spirit. Now C. Baxter Kruger's 'The shack revisited' guides listeners into a deeper understanding of these three persons to help listeners have a more profound connection with the core message of "The shack" that God is love.